An Investigation of the Relationship between Prospective Teachers' Self-Management and Self-Control Skills, Metacognition and E-Mobile Learning Readiness Perceptions - Gözüm Ali İbrahim Can; Demir Özden (Sciendo, 2022)
Introduction: This study aims to investigate the relationship between prospective teachers' self-management and self-control skills, metacognition, and e-mobile learning readiness perceptions.